Trade and wage inequality, mirage or reality? - Gian Maria Tomat (Luxembourg Income Study (LIS), 2010)
In the 2X2X2 Heckscher-Ohlin model there exists a one to one relation between relative good prices and relative factor prices. A change in the relative price of one good changes the relative price of the factor used intensively in the production of the good in the same direction. We review this relation in the context of an analysis of European wage inequality. During the 1980-2000 period wage inequality in Europe increased. However, this movement is not explained by changes in wage differentials by skill level. The education and experience wage premiums remained relatively constant over the sample period. The largest fraction of the increase in wage inequality is accounted by residual inequality.
Keywords: D31; F16; J31; 330; Inter-industry Trade; Intra-industry Trade; Product Differentiation; Wage Inequality; Lohnstruktur; Produktdifferenzierung; Intraindustrieller Handel; Außenhandel mit Industriegütern; EU-Staaten